Schneider, A. & Wright, C. (ed.). Contemporary art and anthropology, Oxford/Nova York, Berg, 2006, 220p. - Stéphane Malysse (Revista de Antropologia, 2005)
Resenha: Entre arte e antropologia: diálogos e apropriações